Longitudinal evaluation of breast tissue in healthy infants: Prevalence and relation to reproductive hormones and growth factors - Ljubicic, Marie Lindhardt; Madsen, Andre; Upners, Emmie N.; Fischer, Margit Bistrup; Busch, Alexander Siegfried; Frederiksen, Hanne; Johannsen, Trine Holm; Juul, Anders; Hagen, Casper P. (Frontiers in Endocrinology, 2022)
Purpose: Breast tissue in infancy is a rather undescribed phenomenon. We aimed to describe the prevalence and progression of palpable breast tissue in healthy boys and girls aged 0-1 years and to evaluate clinical markers, individual serum hormone concentrations as well as combined hormone profiles as determinants of the persistence of breast tissue. Methods: In total, 233 term infants (119 boys, 114 girls) were included and followed from birth until 1 year of age in The COPENHAGEN Minipuberty Study (ClinicalTrials.gov #NTC02784184). Infants were followed up to six times with a clinical examination and serum sampling. Principal component analyses (PCAs) produced combined hormone profiles. Results: A total of 98% of all infants aged 0-1 year exhibited breast tissue at some point. 50% still had breast tissue present at 0.5-0.6 years in girls and 0.3-0.4 years in boys (‘persistent’). At one year, more girls than boys had breast tissue present (p=0.010). Most clinical and hormonal markers did not differ in infants with/without persistent breast tissue. However, in those with persistent breast tissue, estradiol (first visit, girls, p=0.034), androstenedione, corticosterone, cortisol (first visit, boys, all p<0.050), length (first visit, boys, p=0.030), and testicular volume (0.3-0.4 years, p=0.040) were higher, while IGF-I (0.3-0.4, boys, p=0.033) was lower. In boys, a combined, PCA-derived hormone profile (first visit) was able to predict the persistence of breast tissue (area under the curve=83%) better than any single marker. Conclusion: Palpable breast tissue in infancy is common in both sexes although it persists in significantly more girls than boys at one year of age. Data supports both the early origin of breast tissue (in utero- and early postnatal) as well as a role of endogenous hormone production in later development and maintenance.